The psychological distress and care needs of mesothelioma patients and asbestos‐exposed subjects: A systematic review of published studies. Issue 5 (25th March 2018) - Bonafede, Michela; Ghelli, Monica; Corfiati, Marisa; Rosa, Valentina; Guglielmucci, Fanny; Granieri, Antonella; Branchi, Claudia; Iavicoli, Sergio; Marinaccio, Alessandro
Abstract : Background: The purpose of this study is to present the results of a systematic review of published research that focuses on psychological aspects of malignant mesothelioma patients and asbestos‐exposed people. Methods: Our research includes primary studies published between 1980 and 2016, using information from the Cochrane Library, the Psychology Behavioral Sciences Collection, PsychINFO, PubMed, PubGet, PubPsych, and Scopus, in compliance with PRISMA guidelines. Results: We identified 12 papers that investigated the psychological distress and care needs of mesothelioma patients, and nine papers for asbestos‐exposed subjects. Conclusions: This paper highlights the paucity of studies on the psychological distress and care needs of mesothelioma patients and asbestos‐exposed subjects. It confirms that malignant mesothelioma is associated with the physical, emotional, and social functioning of patients, while also suggesting that the risk of developing asbestos‐related diseases among asbestos‐exposed subjects is associated with high levels of psychological distress, despair, and mental health difficulties.